Танцювальний фольклор у творчості Лесі Українки - Богород, А. (Народна творчість та етнографія, 2006)
It was quite popular tradition among the writers in the past to record folklore in the places where they lived or worked. For instance, Lesya Ukrainka was collecting folk songs, games and traditional dance culture all her life. She also used these materials in her writings. Her folk recordings are very valuable materials for contemporary folklorists and ethnomusicologists.